2016
DOI: 10.1155/2016/2503267
|View full text |Cite
|
Sign up to set email alerts
|

Bioenergy and Breast Cancer: A Report on Tumor Growth and Metastasis

Abstract: As many as 80% of the 296,000 women and 2,240 men diagnosed with breast cancer in the United States will seek out complementary and alternative medicine (CAM) treatments. One such therapy is Healing Touch (HT), recognized by the National Center for Complementary and Integrative Health (NCCIH) as a treatment modality. Using a multiple experimental groups design, fifty-six six- to eight-week-old Balb/c mice were injected with 4T1 breast cancer tumor cells and randomly divided into intervention and positive contr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 31 publications
(43 reference statements)
0
4
0
Order By: Relevance
“…B reast cancer (BC) is the most common cancer amongst women globally and also is a major cause of cancer-related deaths among women in developed and developing regions [Ferlay et al, 2015]. It has been reported that most of the BC mortality cases were promoted by spreading of cancer cells to other parts of the body, which in turn promoted disorderly growth, extracellular matrix decomposition, extravasation, metastatic cells into the blood circulation, thus resulting in death [Gronowicz et al, 2015;Running et al, 2016]. Molecular characteristics of gene expression in cancer tissue related to recrudesce of BC have been distinguished by various methods based on the application of DNA arrays [Paik et al, 2004].…”
mentioning
confidence: 99%
“…B reast cancer (BC) is the most common cancer amongst women globally and also is a major cause of cancer-related deaths among women in developed and developing regions [Ferlay et al, 2015]. It has been reported that most of the BC mortality cases were promoted by spreading of cancer cells to other parts of the body, which in turn promoted disorderly growth, extracellular matrix decomposition, extravasation, metastatic cells into the blood circulation, thus resulting in death [Gronowicz et al, 2015;Running et al, 2016]. Molecular characteristics of gene expression in cancer tissue related to recrudesce of BC have been distinguished by various methods based on the application of DNA arrays [Paik et al, 2004].…”
mentioning
confidence: 99%
“…6 Similarly, Balb/C/4T1 mice exposed to a hands-on method of healing showed a trend of smaller tumors in as early as 10 days. 11 Whether this might be due to the limitations of recording technology or information outside the normal electromagnetic field spectrum remains unknown. Further investigations are necessary to determine the viability of this approach when compared to the traditional hands-on approach.…”
Section: Discussionmentioning
confidence: 99%
“…In an independent study reminiscent of this observation, researchers reported a moderate effect of HT on tumor progression in the 4T1/Balb/c model. 11 Those investigators exposed mice injected with tumor cells to HT in sessions of 10 minutes every day or every other day over a period of 10 days. Although no statistically significant difference was reported in that study, the tumor in control mice (ie, not exposed to HT and housed in a separate room) tended to be bigger than those in the mice exposed to HT.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It reported that during the application of bioenergy, which is one of the biofield therapies, the heat generated because of metabolic activities and the bioenergy created by the ion movements in the tissues transferred from one person to another by touching or not (5)(6)(7). The transfer of bioenergy provided through the chakras, which are the energy centers of the body, and the aura associated with these energy centers (8)(9)(10)(11)(12). It is stated that if the chakras, which play a role in receiving and transmitting energy, are blocked, the body has difficulty in maintaining its health, its bioenergy decreases and diseases occur (12).…”
Section: Introductionmentioning
confidence: 99%